ATR-FTIR and spectroscopic methods for analysis of black seed oil from alginate beads - Alkhatib, Hamzeh; Mohamed, Farahidah; Doolaanea, Abd Almonem (2018)
Objective: This study aimed to use attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR) for rapid quantification of black seed oil (BSO) from alginate beads and to develop simple analysis method for in vitro release study based on turbidity measurement. Methods: Guluronic acid-rich (high-G) sodium alginate was used to encapsulate BSO with the aid of Tween 80 as a stabilizer. ATR-FTIR method was developed for quantification of encapsulation efficiency of BSO by applying Beer-Lambert law after selection of a few wave number combinations. UV-vis method based on measurement of emulsion turbidity at 600 nm was also developed to quantify BSO during the releasing from alginate beads in simulated intestine buffer. Results: ATR-FTIR method exhibited linearity in the range of 25-300 mg BSO /ml emulsion (mg BSO /ml E )with R 2 =0.998, RSD=8.4%, LOD=0.28 mg BSO /ml E and LOQ=0.87 mg BSO /ml E . BSO-alginate beads was found to completely encapsulate BSO with around 100.5% efficiency. UV-vis method exhibited linearity in the range of 50-300 mg BSO /ml E , R 2 =0.9931, RSD=1.34%, LOD=0.89 mg BSO /ml E, and LOQ=2.71 mg BSO /ml E . In addition, the method showed that total amount of BSO was released at 110 min. Conclusion: These methods are considered as a practical method for quantification of BSO for encapsulation efficacy and release. They will help to accelerate and improve routine characterization of encapsulated BSO in food and pharmaceutical technology.